RESEARCH OF THE CHARACTERISTICS OF A STEGANOGRAPHY ALGORITHM IN IMAGES WHEN USING DIFFERENT ALPHABET (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Steganography can be defined as a method of hiding data in cover media so that others are not aware of its existence. Steganographic systems play an important role in the covert transmission of information even in the presence of a steganalyser. The article deals with the steganography system which hides text inside images without losing data in components of RGB model. The secret message is hidden in the cover image using Least Significant Bit algorithm. The statistical characteristics of stego-images with the embedded information in Cyrillic and Latin are investigated. The aim of the study is to determine whether there is a change in the qualitative characteristics of the stego-image, when it is hidden the same information, but was used different alphabets. The comparative results for the proposed algorithm are very promising for Cyrillic alphabet. To evaluate steganography system properties are used the measures like Signal-to-Noise Ratio, Peak Signal-to-Noise Ratio, Mean Squared Error and Structural Similarity Index for measuring.